Evaluación de la calidad organoléptica a camarones litopenaeus vannamei en planta descabezadora - Córdova Paladines, Olger Vinicio (2013)
The purpose of this research is to identify the area of production of shrimp you entered with better organoleptic analysis according to income during the eleven primary plant watering places in different months. The control plan national plays an important role with respect to different product quality processes, it is executed and implemented by the National Fisheries Institute, the institution controls the various companies engaged in processing fish products. We evaluated various factors such as the organoleptic defects such as pitting and texture, and water holes in different months of the year, each batch is done entering the respective analysis to determine the quality of shrimp to be processed. The organoleptic analysis method is what sensory analyzes evaluated the same as keeping records are sorted and are part of the traceability that is reviewed by the agencies. The method for measuring texture and defects such as chopped shrimp was gotten by the different percentages of samples analyzed during the six months of all the shrimp you entered during that period. The three study areas reported high and acceptable organoleptic quality, what we can say that it is working properly in different shrimp to control odors, flavors and defects in the shrimp, keeping our product is derecognised exporters in class and to be competitive with other countries